Comparison of Organochlorine Pesticide Residues in Freshwater Fish, Mollusks and Sediments from Five Main Fishing Areas in Vientiane, Laos - Boutah, Southavilay (2004)
The use of organochlorine pesticides in rice growing in Laos is widespread. Potential contamination of pesticides to the aquatic organisms and sediments is a major concern. This study investigates the organochlorine pesticide contamination in fish, mollusks, and sediment from five main fishing areas of Vientiane, the capital of Laos. The fishing areas are located within the rice fields around Vientiane.